2022
DOI: 10.1038/s41598-022-16361-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards a data-driven system for personalized cervical cancer risk stratification

Abstract: Mass-screening programs for cervical cancer prevention in the Nordic countries have been effective in reducing cancer incidence and mortality at the population level. Women who have been regularly diagnosed with normal screening exams represent a sub-population with a low risk of disease and distinctive screening strategies which avoid over-screening while identifying those with high-grade lesions are needed to improve the existing one-size-fits-all approach. Machine learning methods for more personalized cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For instance, the My CancerIQ tool for cervical cancer risk assessment prompts users to inquire about factors influencing their cervical cancer risk, such as age, smoking habits, and family cancer history. Subsequently, the tool computes the user's risk by referencing studies involving individuals aged ≥ 40 years with no prior cancer history [50]. Apart from online tools, precision medicine strategies utilizing genomic applications and digital health interventions can also offer individualized risk evaluations for cervical cancer.…”
Section: Individualized Risk Evaluationmentioning
confidence: 99%
“…For instance, the My CancerIQ tool for cervical cancer risk assessment prompts users to inquire about factors influencing their cervical cancer risk, such as age, smoking habits, and family cancer history. Subsequently, the tool computes the user's risk by referencing studies involving individuals aged ≥ 40 years with no prior cancer history [50]. Apart from online tools, precision medicine strategies utilizing genomic applications and digital health interventions can also offer individualized risk evaluations for cervical cancer.…”
Section: Individualized Risk Evaluationmentioning
confidence: 99%
“…We opted to create new models instead of validating or updating existing ones due to variations in target populations, measurement procedures, changes over time and access to the nationwide health data. Although the models promise potentially e cient estimation of outcomes, cervical cancer prediction model development and validation remains in its infancy, grappling with the challenges of re ning its algorithms and data sources 24 . Following internal validation, external validation, and randomized controlled trials are essential steps to further validate the model's performance across diverse populations and settings, ensuring robustness and generalizability in clinical practice.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…In an optimized risk-based scenario, the individual risk of developing CIN2+ would determine the intensity of the follow-up trajectory, improving the population benefit-harm ratio. A recent study has indeed shown that accurate risk classification can be improved to develop a personalized cervical cancer screening program [ 19 ].…”
Section: Introductionmentioning
confidence: 99%